Use of Cryotherapy for Managing Epistaxis in the First Aid Setting: A Scoping Review - Berry, David (Cureus, 2021)
Epistaxis, or nosebleed, is bleeding from the nostril(s), nasal cavity, or nasopharynx. Anterior nasal bleeding is the most common location for spontaneous nontraumatic epistaxis and is commonly treated with manual compression to the nasal alae. Cryotherapy is also routinely recommended in conjunction with manual compression in the first aid and ED setting. We performed a scoping review on behalf of the International Liaison Committee on Resuscitation First Aid Task Force guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR). We searched Embase, Cochrane, and PubMed databases for published studies, without date restrictions, and we searched the gray literature using Google.com and Google Scholar. The websites of selected resuscitation councils were searched for guidelines relating to the management of epistaxis. References from included studies were hand-searched. Our published and gray literature search identified 1255 and 61,315 records, respectively. After removing duplicates and following selection criteria, we included 21 records from the published literature and 11 records from the gray literature. Our scoping review found that most of the published studies and website documents focused on managing nontraumatic epistaxis in the first aid setting. They provide recommendations for the use of cryotherapy based on expert opinion or indirect evidence extrapolated from cryotherapy-associated changes in nasal submucosal temperature, nasal blood flow, and nasal blood volume in healthy subjects (three studies). We did not identify any prospective, randomized trials comparing the efficacy of cryotherapy as an intervention for nontraumatic epistaxis in the first aid setting. The limited literature identified in this scoping review does not support the development of a systematic review but highlights the need for future research to better understand the role of cryotherapy in the first aid setting.